Gastro-Intestinal Parasites in Monkeys of Shivapuri Nagarjun National Park and Temple Areas of Kathmandu Valley - Jain, Payal; Maharjan, Babita (Amrit Research Journal, 2023)
The study intended to assess the prevalence of gastro-intestinal parasites in free-ranging macaques of Bajarayogini temple, Bajrabarahi temple and areas of Shivapuri Nagarjun National Park (SNNP). A total of 70 fresh fecal samples of Macaca sps, were collected from October 2022 to May 2023 and processed by direct wet mount method and concentration method. The result disclosed the distribution of total 5 species of protozoan parasites and 8 species of helminth parasites, indicating 100% prevalence rate where Entamoeba coli (67.14%) showed the highest prevalence followed by Trichostrongylus spp. (1.43%) with the lowest prevalence. It was observed that the helminth parasite, Nematodirus spp. was identified for the first time from the samples of monkeys in Nepal. Human-primate transmission of infectious disease is one of the most important emerging threats that’s why, emphasizing public awareness for control of parasitic infection to reduce the zoonotic transmission of the pathogenic parasites was suggested.